New dimensions and options in conservation agriculture - Biswas, A.K.; Somasundaram, J.; Hati, K.M. (Indian Journal of Agroforestry, 2020)
Widespread residue burningcoupled with intensive tillage accelerates oxidation of organic matter resulting in elevated levels CO2 in theatmosphere thereby contributing to the greenhouse effect and global warming of the planet. Besides, land degradation is serious environmental problem that threatens soil health and food security. Conservation agricultural (CA) practices helps in reversing these trends.CA refers to the system of raising of crops in rotation without tilling or with minimal disturbances to the soil while retaining crop residues on the soil surface. Conversion of conventional practices into conservation agriculture practices helps in sequestration of soil organic carbon (SOC), enhanced soil health and mitigation of climate change effect, besides better soil aggregation, nutrients cycling, and reduction of soil erosion and nutrient losses.CA practices have been proposed as a widely adapted set of management principles that can assure more sustainable agricultural production. Worldwide, CA spreads in about 124 mha, which is aimed to conserve, improve and make more efficient use of natural resources through integrated management of available soil, water and biological resources combined with external inputs. It contributes to environmental conservation as well as economically, ecologically and socially sustainable agricultural production. The location specific CA farm machinerydevelopment and technology generation–dissemination–adoption of CA technologies has to be looked into for broader perspective with interdisciplinary approach. Large scale capacity building at different levels like training farmers, land managers, students, extension faculties and scientistsfor adoption of CA practicesis the need of the hour.